Nekaj kritičnih misli o kriminalitetni politiki na področju gospodarstva - Bavcon, Ljubo (Pravnik, 2017)
The author emphasizes that economic crime indeed eludes unambiguous and robust criteria for distinguishing between business practices, which are normal in commercial transactions in a capitalist society - a risk society - and practices that are clearly criminal. However, this fact could not justify the immense and arbitrary spread of criminalization in this area. The author emphasizes an increased penetration in this area of criminal law of the applicable criteria characteristic of civil law. Thus, in particular, the criminal offenses of abuse of office or trust and commercial fraud are subjects of immense spread of incriminations, which opens the door to any arbitrariness of the ruling political elite. The latter already at the onset of the penetration of neoliberal variant of capitalism declared the economic crime as a phenomenon which threatens the very existence of a democratic social order, reminding us of a similar move some fifty years ago by the then Eastern European leaders who proclaimed political crime to be a phenomenon that threatens socialism. However, today in all western countries and also in Slovenia, the democratic social order and its core values, such as tolerance, the rule of law, and human rights, are threatened by the response against this phenomenon using exclusively criminal repression. Therefore, the author warns against the abuse of criminal law for its essentially opposing goals, such as solving the political, economic and social problems and conflicts. The author concludes by encouraging such criminal justice policy in general and especially in the economic sphere, which would be based on professional and scientific analyses, which would be moderate and reasonable, and which would not serve as a means of governance and political feuds. Simultaneously, he encourages the formation of such an environment in which the enforcement authorities could safely operate legitimately, legally, professionally correct, and fairly, which is the criterion for their maximum efficiency.
Keywords: criminal law; gospodarska kriminaliteta; gospodarsko poslovanje; kazensko pravo